Las relaciones interpersonales de los grupos étnicos: indígenas, afroecuatorianos y mestizos. - Tigmasa Mena, Yesenia Lisbeth (2018)
This work research called The Interpersonal relationship of the Ethnic groups: Indigenous, Afro-Ecuadorian, Mestizo people, it was carried out with the purpose of identifying the consequences of discrimination and the level of acceptance of the puplis in the classrooms because these children groups have to move on big cities with these families in order to find a better lifestyle. The object of study focuses on how the interpersonal relationships of children of different ethnic groups, who study at “Econ. Abdón Calderón Elementary School” from La Ecuatoriana Parish, Quito Canton, Pichincha Province, the methodological design is part of a qualitative method through field research with the application of surveys, in addition to the documentary literature review, allowed to support the analysis and discussion of the results, thus in this way a descriptive level was reached, the following results have been obtained of what is happening in the educational center, there is racism towards students of different ethnic groups, which shows that there is no respect for the customs and traditions where students come from, teachers must work more in the integration of the students within and outside the classroom using different strategies with work to improve interpersonal relationships.